Funções reais que preservam a soma - Souza, Mafalda Balbino de (2022)
In this work, we want to show examples of real functions that preserve the sum, including those of the linear form (f(x) = cx) and those that do not have this form. For that, we will initially talk about the Affine Function, the Linear Function, then we will bring definitions such as Hamel's Base and Zorn's Lemma. In possession of such results and concepts, We will end with examples of the desired functions.